Enquête sur l’implication des habitants dans la conception d’un petit lotissement parisien des années 1920 : le square de Montsouris - Lucie Prohin (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This article looks at the houses built in the early 1920s by architect Jacques Bonnier for the Société anonyme coopérative d’habitations à bon marché du parc de Montsouris, a low-cost housing cooperative. Taking advantage of the many administrative and architectural sources available on this project, the aim is to examine the degree of agency the future users had in the design process of their own homes. After a brief historical contextualization, the article goes on to look at the identity of the purchasers of the low-cost houses in the square de Montsouris. In the light of this information, it analyses the way in which the project was run — between the architect's pre-design of the dwellings and the adaptations to the residents’ needs. This leads us to reflect on the singular place of this housing estate in the landscape of social and popular housing during the interwar period.